Membangun Keterbukaan dalam Ruang Virtual: Dinamika Interaksi dan Proses dalam Konseling Kelompok Berbasis Virtual - Dinda Rossa Aldyan Virera; Muslikah (Jurnal Muria Research Guidance and Counseling (MRGC), 2026)
This study aims to describe the interaction dynamics and group processes in virtual - based group counseling. The novelty of this study lies in its focus on exploring interaction patterns, self-disclosure, group cohesion, and group development processes in virtual counseling settings through a descriptive qualitative approach. The study employed a descriptive qualitative method using literature review techniques from various scientific sources, including journals, books, and relevant academic publications published between 2019 and 2026. The findings indicate that virtual group counseling has different interaction characteristics compared to face-to-face counseling. Virtual settings provide flexibility and encourage greater self-disclosure among group members, but also present challenges related to nonverbal communication, emotional engagement, and member participation. In addition, group development processes continue to occur through forming, storming, norming, and performing stages, although they tend to be more implicit. Therefore, counselors need additional competencies in digital communication and virtual group management to support effective counseling processes.